Funcionamento executivo em controladores de tráfego aéreo do sul do Brasil - Freitas, Ângela Maria de (2016)
Objectives: To evaluate the executive functions of air traffic controllers (ATCO) and relate them to characteristics of professional activity, such as length of service, technical qualification and work shifts. Additionally, to evaluate stress and excessive daytime sleepiness in ATCO, identifying the impact of these variables on attention activity. Methods: Fifty-two ATCO participated, based at 3 air traffic control units (A, B and C). Sample selection adopted a non-probabilistic convenience approach with sequential selection. Results are presented as descriptive statistics using absolute and relative distribution (n-%), as well as by measures of central tendency and variability, with the distribution of data evaluated using the Shapiro–Wilk test. Pearson's chi-squared (χ2) or Fisher's exact test was used to compare between qualitative variables. The Mann-Whitney or Student t test was applied for comparison of continuous variables between two independent groups, and One-way Analysis of Variance with post-hoc Tukey for comparison between three or more groups. Instruments: Wisconsin Card Sorting Test (WCST), Diffuse Attention Test -TEDIF-III, Focused Attention Test -TECON-III, Letter-Number Sequencing -WAIS III, Digit Span -WAIS III, Matrix Reasoning -WAIS III, Lipp Inventory of Stress Symptoms for Adults (ISSL-Lipp), Epworth Sleepiness Scale (ESS) and Questionnaire applied to the ATCO. Results: The ATCO presented mean scores above the population mean for assessment of cognitive flexibility, strategic planning and ability to generate solutions, especially among the group of controllers with 0-5 years of service, whose scores were statistically significant. Considering the Digits, Letter-Number Sequencing and Matrix Reasoning subsets, the ATCO presented weighted scores above the mean, indicating efficient performance in working memory, visual information processing and abstract reasoning. The classification of average and below average prevailed in the focused attention evaluation, with these rates being within the population mean. In the diffuse attention test, they presented an increasing growth between the mean number of correct responses and time of task performance, implying an ability to maintain complex diffuse attention, efficient control of interferences and absence of impairment due to time pressure. Only 16% of the ATCO presented stress symptomatology, with a predominance of physical symptoms (62%). In the evaluation of excessive daytime sleepiness (EDS), statistical significance was identified between sleep and place of work. The ATCO with positive EDS scores worked rotating shifts that included the nighttime period. Conclusion: The executive functioning of ATCO is not influenced by shift work, technical qualification or length of service. Executive functioning is associated with the successful performance of key cognitive resources, such as memory, attention abstract reasoning, planning and flexibility to change.